Action research with a proposal to improve the agility of public procurement processes, through the Lean Office - Santos, Scheirla Teixeira; Pereira, Tábata Nakagomi Fernandes (Seven Editora, 2023)
The Lean Office aims to improve the workflow and eliminate existing waste in administrative areas. In this sense, this project aims to understand the applicability of the Lean Office philosophy employed in the procurement process of a public body, answering the following question: which activities do not add value to bidding procedures? For this, action research is used as a research methodology, oriented toward solving the research problem, adopting the process mapping tool to visualize and understand the activities performed in the process. It is intended to obtain as a result the mapping of the current and future value stream and an action plan for the implementation of the future scenario, to reduce the lead time and obtain improved efficiency in the execution of the bidding processes. DOI: https://doi.org/10.56238/devopinterscie-033